Association between serum sodium levels within 24 h of admission and all-cause mortality in critically ill patients with non-traumatic subarachnoid hemorrhage: a retrospective analysis of the MIMIC-IV database - Liu, Junjie; Li, Jianmin; Zhang, Qiuhua; Wang, Liang; Wang, Yichao; Zhang, Jingxi; Zhang, Junwei (Frontiers in Neurology, 2023)
Abstract Objective: We aim to evaluate the relationship between serum sodium and mortality in critically ill patients with non-traumatic subarachnoid hemorrhage. Methods：A retrospective investigation of critically ill non-traumatic patients with subarachnoid hemorrhage (SAH) utilizing the MIMIC-IV database. We collected the serum sodium levels at admission and determined the all-cause death rates for the ICU and hospital.We employed a multivariate Cox proportional hazard regression model and Kaplan-Meier survival curve analysis to ascertain the relationship between serum sodium and all-cause mortality. In order to evaluate the consistency of correlations, interaction and subgroup analyses were also conducted. RESULTS: A total of 864 patients with nontraumatic SAH were included in this study. All-cause mortality in the ICU and hospital was 32.6% (282/864) and 19.2% (166/864), respectively. Sodium levels at ICU admission showed a statistically significant J-shaped nonlinear relationship with ICU and hospital mortality (non-linear P-value < 0.05, total P-value < 0.001) with an inflection point of approximately 141 mmol/L, suggesting that mortality was higher than normal serum sodium levels in hypernatremic patients. Multivariate analysis after adjusting for potential confounders showed that high serum sodium levels (≥145 mmol/L) were associated with an increased risk of all-cause mortality in the ICU and hospital compared with normal serum sodium levels (135-145 mmol/L), (hazard ratio (HR)=1.47, 95% CI: 1.07-2.01, P=0.017) and HR=2.26, 95% CI:1.54-3.32, P<0.001). Similarly, Kaplan-Meier (K-M) survival curves showed lower survival in patients with high serum sodium levels. Stratified analysis further showed that the association between higher serum sodium levels and hospital all-cause mortality was stronger in patients aged <60 years with a hospital stay of <7 days. CONCLUSION: High serum sodium levels upon ICU admission are related with higher ICU and hospital all-cause mortality in patients with nontraumatic SAH. A new reference is offered for control strategies to correct serum sodium levels.